China Coast Pidgin: Texts and contexts - Ansaldo, Umberto; Matthews, Stephen; Smith, Geoff (JOHN BENJAMINS PUBLISHING CO, 2010)
In this paper we revisit some long-standing questions regarding the origins and structure of China Coast Pidgin (CCP), also known as Chinese Pidgin English. We first review the historical context of the China Trade which formed the ecology for the development of CCP. We then review the available sources, focusing on newly transcribed data from Chinese-language instructional materials. These sources provide fresh evidence for grammatical structure in CCP, and demonstrate strong influence from Cantonese as the major substrate language. Comparison with English-language sources shows systematic contrasts which point to likely variation between Anglophone and Sinophone lects, as in the case of wh-questions which show regular wh-fronting in English sources and pervasive use of wh-in-situ in Chinese sources. This conclusion helps to resolve the debate over the Sinitic features of CCP.